2022
DOI: 10.1007/s00167-021-06828-w
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning algorithm to predict anterior cruciate ligament revision demonstrates external validity

Abstract: Purpose External validation of machine learning predictive models is achieved through evaluation of model performance on different groups of patients than were used for algorithm development. This important step is uncommonly performed, inhibiting clinical translation of newly developed models. Machine learning analysis of the Norwegian Knee Ligament Register (NKLR) recently led to the development of a tool capable of estimating the risk of anterior cruciate ligament (ACL) revision (https://swast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
(48 reference statements)
1
25
0
Order By: Relevance
“…Several studies have revealed the performance of machine learning algorithms in predicting PROMs and the risk of reoperation. 10,17,22,29,30 Ramkumar et al 29,30 applied 7 machine learning models to predict whether patients would achieve the MCIDs of PROMs at 2 years after osteochondral allograft transplant, and the AUCs of the best-performing models ranged from 0.60 to 0.94. Haeberle et al 10 reported AUCs ranging from 0.62 to 0.80 for random forest models predicting the risk of subsequent hip surgeries before primary hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed the performance of machine learning algorithms in predicting PROMs and the risk of reoperation. 10,17,22,29,30 Ramkumar et al 29,30 applied 7 machine learning models to predict whether patients would achieve the MCIDs of PROMs at 2 years after osteochondral allograft transplant, and the AUCs of the best-performing models ranged from 0.60 to 0.94. Haeberle et al 10 reported AUCs ranging from 0.62 to 0.80 for random forest models predicting the risk of subsequent hip surgeries before primary hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kunze et al, 17 a history of contralateral knee surgery, preoperative knee extension, medial collateral ligament examination, femoral fixation, and BMI were the top 5 features for predicting achievement of the IKDC score MCID, whereas the preoperative IKDC score, the top predictor of our study, was less important. Furthermore, Martin et al 22 analyzed a national knee ligament registry and developed a revision risk calculator for ACLR using only 5 predictive variables (age, preoperative Knee injury and Osteoarthritis Outcome Score [KOOS] Quality of Life subscale, graft choice, femoral fixation, and time from injury to surgery) based on the Cox Lasso model, with a concordance of 0.68. The disparate top predictors in our study may be attributed to the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Recent predictor studies [ 40 – 44 ] harnessed statistical methods, including but not limited to multivariable logistic and linear regressions, Kaplan-Meier survival curves, and Cox proportional hazards models to predict the influence of treatment variables on superior or inferior PROMs and assess the risk of revision ACL surgery over time, respectively, while aiming to account for the complex interaction between a large number of factors. Also, a couple of registry-based studies have already harnessed the use of artificial intelligence (AI) and machine learning (ML) technology in order to predict outcomes following treatment of ACL injury [ 45 •, 46 •]. With the emerging role of AI and ML, registry data will likely enable the development of algorithms designed to predict the individualized risk of ACL-R failure and inferior patient outcomes based on treatment variables [ 45 •, 46 •].…”
Section: Methods Used In Registry Studiesmentioning
confidence: 99%
“…Also, a couple of registry-based studies have already harnessed the use of artificial intelligence (AI) and machine learning (ML) technology in order to predict outcomes following treatment of ACL injury [ 45 •, 46 •]. With the emerging role of AI and ML, registry data will likely enable the development of algorithms designed to predict the individualized risk of ACL-R failure and inferior patient outcomes based on treatment variables [ 45 •, 46 •].…”
Section: Methods Used In Registry Studiesmentioning
confidence: 99%
See 1 more Smart Citation